Tunneling, propping, and expropriation: evidence from connected party transactions in Hong Kong☆ - CHEUNG, Y; RAU, P; STOURAITIS, A (Journal of Financial Economics, 2006)
We examine a sample of connected transactions between Hong Kong listed companies and their controlling shareholders. We address three questions: What types of connected transactions lead to expropriation of minority shareholders? Which firms are more likely to expropriate? Does the market anticipate the expropriation by firms? On average, firms announcing connected transactions earn significant negative excess returns, significantly lower than firms announcing similar arm's length transactions. We find limited evidence that firms undertaking connected transactions trade at discounted valuations prior to the expropriation, suggesting that investors cannot predict expropriation and revalue firms only when expropriation does occur.